PMO-118 The effects of th17 cytokines on liver parenchymal cells shape the microenvironment for local generation of TH17/TC17 in inflammatory liver disease. (28th May 2012) - Humphreys, E; Bhogal, R; Munir, M; Muirhead, G; Eksteen, B; Afford, S; Oo, Y; Adams, D
Abstract : Introduction: IL-17 secreting T cells have been implicated in autoimmunity, inflammatory disease and provide a link between the innate and adaptive immune responses. High numbers of IL-17-producing T cells which also secrete IL-21 and IL-22 are found in close proximity to bile ducts in several liver diseases. Th17 related cytokines have multiple effects and may be involved in both effector responses and repair and regeneration. Methods: Primary human parenchymal cells were assessed for cytokine receptor expression by western blotting. The effects of stimulation with recombinant IL-17, IL-21, IL-22, TNFa or IFN-g alone or in combination were compared for apoptosis using annexin staining, proliferation was measured by in situ Ki67 staining and adhesion molecule expression was assessed by flow cytometry. Secretion of IL-1b, IL-6, IL-23 and TGF-b1 was assessed by ELISA. Results: All parenchymal cells expressed IL-17R, IL-21R and IL-22R. Th17 related cytokines did not cause apoptosis but led to parenchymal cell proliferation. Cholangiocytes and hepatocytes responded best to IL-17, whereas sinusoidal endothelial cells were responsive to IL-22. Endothelial cells upregulated adhesion molecules in response to Th17 related cytokines. Cholangiocytes responded to Th17 cytokines by secreting high levels of IL-1b, IL-6, IL-23 and TGF-b1 all cytokines that support the survival of Th17 and Tc17 cells. Conclusion: Liver parenchymal cells express IL-17, IL-21 and IL-22 receptors and proliferate in response to Th17 cytokines. Upregulation of adhesion molecules by sinusoidal endothelial cells promotes lymphocyte recruitment and retention. Cholangiocytes also respond by secreting Th17 /Tc17 polarising cytokines. Therefore Th17 related cytokines secreted by infiltrating lymphocytes may activate the epitheliome to generate a local environment characterised by cholangiocyte proliferation and Th17 /Tc17 cell survival, thus contributing to bile duct proliferation and persistent chronic inflammation that characterises many liver diseases. Competing interests: None declared.